The hygienism in argentine social work´s history in the beginnings of the XX century (Papeles, 2023)
The purpose of this article is to present an analysis of the professional field´development fundamentals in the origins of Social Work in Argentina, particularly taking as a reference the institutions and debates which took place in Capital Federal and its most nearby geographic zone of influence: the Buenos Aires province.These reflections are product of an investigation and postgraduate work process which aimed to identify what social-historic forces intervened in the profession´s consolidation: that is to say, what impacts had the social, politics, economical and cultural contradictory tensions of that time -between the years 1920-1955-, and what were the thinking bases which influenced in the organization of the first formation´s spaces and that, at the same time, configured the way of thinking the intervention from the institutions in which this new professionals were set in. For that, the analysis of that time´s documents and an exhaustive revision of the medical hygienists´ influence were essential, recognising the tensions and disputes related to how to organize the social public assistance in institutional and professional terms.
Keywords: eugenics; biotypology; hygienism; institutionalization; professionalization